Conceptualizing shariah internal audit’s objectives and effectiveness within corporate governance: a preliminary study / Noor Fadhzana Mohd Noor and Noor Affendi Ismail - Mohd Noor, Noor Fadhzana; Ismail, Noor Affendi (Academy of Contemporary Islamic Studies (ACIS), 2021)
In Shariah Governance 2019, Shariah Internal Audit constitutes a significant function within the IFIs. In view of this, its effectiveness is an important issue. Based on the literature review, prior studies have employed goal model, functional approach mode and strategic constituency model to measure the effectiveness of the SIA or Shariah audit. What is still lacking is the use of system resource model of effectiveness. The system resource model entertains individual entity or IFIs as the focal point of effectiveness. Thus, it offers the effectiveness to be measured based on the objectives of the Shariah Internal Audit, practices and policies. In order to do this, the objectives of the Shariah Internal Audit must first be determined. Thus, this study was conducted to determine the objectives of Shariah Internal Audit based on the Corporate Governance of the Islamic Financial Institutions. It is a preliminary and exploratory research. Content analysis was employed on data collected from relevant literature, legislations and selected Corporate Governance Disclosure. This study found that the objectives and effectiveness frameworks of Internal Audit employed for individual institutions are different from each other. Hence, the effectiveness must be measured individually. The implications of this study are that the findings may be useful for future empirical studies on the effectiveness of Internal Audit and Shariah Internal Audit of the Islamic Financial Institutions in Malaysia.